FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KEDAI KEBAB MUBAROK DI PATI - Fauziyah, Niswatul; Ramadhan, Gifani; Octavia, Ayu Nurafni (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This study aims to analyze the influence of price perception, taste and service quality on purchasing decisions. The population in this study were all consumers of Kebab Mubarok Shop. Data were obtained through a questionnaire distribution method using a puposive sampling technique. The sample used was 96 consumers, the data obtained from the distrbution of questionnaires will be analyzed using SPSS. The results of the quantitative analysis include validity tests, reliability, classical assumption tests, multiple linier regression analysis, hypothesis testing through t-tests, F-tests and determination coefficient analysis (R2). The results of partial testing indicate that the price perception variable has a positive and insignificant effect on purchasing decision, the taste variable has a positive and significant effect on purchasing decisions, the service quality variable has a positive and significant effect on purchasing decisions. The results of simultaneous testing indicate that the price perception variable, taste and service quality have a significant effect on purchasing decisions of Kebab Mubarok